IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 TERHADAP PELAKSANAAN PERJANJIAN YANG BEROBJEK JAMINAN - Hasani, Jazau Elvi; Trianingsih, Fitri Agustina; Rizky Saraswati, Nadiya Ayu (Jurnal Hukum Magnum Opus, 2020)
Abstract A fiduciary guarantee is a law product that is applied to protect creditors in particular. When the debtor defaults, the creditor can request compensation from the debtor through execution of a fiduciary guarantee. The Constitutional Court (MK) issued Decision Number 18 / PUU-XVII / 2019 related to the application for judicial review of Law Number 42 of 1999 concerning Fiduciary Guarantees Article 15 paragraph 2 and Article 15 paragraph 3 of the 1945 Republic of Indonesia Constitution. The Constitutional Court granted the petitioners part of the petition, stating Article 15 paragraph (2), Article 15 paragraph (3), and Elucidation of Article 15 paragraph (2) of Law Number 42 the Year 1999 concerning Fiduciary Security contradicts the 1945 Constitution and has no legal force binding. Application related to the implementation of Article 15 paragraph (2) and paragraph (3) of Law No. 42/1999 concerning Fiduciary Guarantee which subsequently reads following Article 15 paragraph (2) "Fiduciary Guarantee Certificate as referred to in paragraph (1) has the same executorial power as a court decision that has obtained permanent legal force" and Article 15 paragraph (3) that "If the debtor fails to promise the Fiduciary Recipient has the right to sell the object that is the object of the Fiduciary Guarantee on his authority". Based on the above, the author considers it necessary to discuss what is the background of the petitioner in submitting an application to the Constitutional Court, the Court's argument in deciding the case, and the implications of the decision on the implementation of the agreement with a fiduciary guarantee before and after the Constitutional Court Decision Number 18 / PUU-XVII / 2019.Keywords: constitutional court decision; guarantee; implicationAbstrak Jaminan fidusia adalah produk konvensional yang memberi perlindungan hukum kepada kreditur. Ketika debitur wanprestasi, kreditur meminta ganti rugi dengan eksekusi jaminan fidusia. Mahkamah Konstitusi (MK) mengeluarkan Putusan No 18/PUU-XVII/2019 terkait permohonan pengujian materi Undang-Undang No 42/1999 tentang Jaminan Fidusia terhadap Konstitusi atau Undang-undang Dasar Negara RI 1945. Melalui putusan tersebut Mahkamah Konstitusi mengabulkan permohononan pemohon sebagian, dengan menyatakan bahwa Pasal 15 ayat (2), Pasal 15 ayat (3), dan Penjelasan Pasal 15 ayat 2 UU Nomor 42/1999 Jaminan Fidusia telah bertentangan dengan UUDNRI 1945 sehingga tidak berkekuatan hukum mengikat. Permohonan terkait keberlakuan UU No 42/1999 tentang Jaminan Fidusia yang Pasal 15 ayat 2 berbunyi bahwa Sertifikat Jaminan Fidusia memiliki kekuatan eksekutorial yang sama dengan putusan pengadilan berkekuatan hukum tetap dan Pasal 15 ayat (3) yang menyatakan bahwa bila debitur cidera janji, Penerima Fidusia berhak menjual Benda objek Jaminan Fidusia. Atas dasar diatas penulis menilai perlu untuk membahas apa latar belakang pemohon dalam mengajukan permohonan kepada Mahkamah Konstitusi, argumentasi Mahkamah dalam memutus perkara tersebut, dan implikasi putusan tersebut terhadap pelaksanaan perjanjian yang berobjek jaminan fidusia sebelum dan sesudah Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 .Kata kunci: jaminan fidusia; implikasi; putusan mahkamah konstitusi